The Customer Satisfaction Analysis of Community based Agrotourism in Yogyakarta - Indrayanti, Temy; Jamhari, Jamhari; Mulyo, Jangkung Handoyo; Masyhuri, Masyhuri (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Several kinds of agro-tourism are managed by the community and by the private sector. However, if agro-tourism is managed by the community, can it give satisfaction to the visitors? This study aims to determine the level of customer satisfaction by Customer Satisfaction Index (CSI) and to investigate what marketing mix attributes should be improved by IPA-Kano integration analysis. The research method used was a quantitative research on community-based Salak (Salacca zalacca) Agro-tourism in each category of tourism village, namely ’growing’, ‘developing’ and ‘independent’ tourism village categories. The measurement of visitor satisfaction used the marketing mix attributes of 7Ps (price, place, product, promotion, process, people and physical evidence). Based on the results of CSI, the services provided by the community-based salak agro-tourism manager are considered ‘Satisfied’ in the Growing and Developing agro-tourisms and ‘Very Satisfied’ in the Independent agro-tourism. Priority attributes that should be improved are attributes included in the ‘Fatal’ category. Priority attributes in ‘growing’ agro-tourism are the marketing activities (publicity), availability and cleanliness toilet. Priority attributes in ‘developing’ agro-tourism are marketing activities (promotion), availability and cleanliness of toilets. Priority attributes in ‘independent’ agro-tourism are availability and cleanliness of toilets.